Literacy and Numeracy Application “TOY App”: Students' Responses - Wahyu Kyestiati Sumarno; Ali Shodikin; Nur Imro’atus Solikha; Novandi Kevin Pratama; Brigita Febi Valensiana (Future Science, 2022)
Literacy and numeracy skills are the minimum competencies that students need to learn. However, many studies show that the literacy and numeracy level of students in Indonesia is still very low, including English literacy. TOY APP is an Android-based application designed as an independent learning tool. It tries to make the learning process becomes easier and more fun. It facilitates literacy practices in Bahasa Indonesia, English, as well as numeracy for elementary school students. This study aims to examine the effectiveness of the TOY App application based on the student’s responses. This study is research and development research that followed the Thiagarajan development procedures. The subjects of this study were 10 elementary school students. Data collection techniques were carried out with an interview-based questionnaire. The results of this study indicate that this application received a very good response from the students seen from the elements of easiness, functionality, appearance, and whether it increases curiosity. This means that the application has been developed is ready to be used as a means of an independent learning tool to increase the literacy and numeracy levels of students.